The gift of volunteering and the virtues of self-love - Puckering, Jo (Traditiones (Ljubljana), 2014)
This article outlines some of the intellectual, social and political relationships between contemporary interpretations of gift exchange and volunteering in Higher Education. It questions often dichotomous ways of understanding volunteering as altruistic or self-interested, explores changing uses and expectations of volunteering in Western society, and considers the rhetoric and realities of volunteer support, motives and experiences, in relation to institutional priorities and drivers.
Keywords: cultural anthropology; kulturna antropologija; ethics; etika; altruism; altruizem; solidarity; solidarnost; social work; socialno delo; high schools; prostovoljstvo; prostovoljci; visoko šolstvo; Velika Britanija